Development of Korean-Style Fish Cake Mixed with Lokan (Polymesoda expansa), Physicochemical Properties, and Its Acceptability (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Lokan (Polymesoda expansa), a mollusk with high nutritional value, is often overlooked due to its unappealing texture and color. This study explores the feasibility of incorporating Lokan meat into Korean-style fish cakes (KSFC) to enhance its utilization. The minced Lokan was blended with surimi, wheat flour, cassava flour, egg white powder, oil, and water, and then steamed in molds. A panel of 30 individuals evaluated the KSFC with varying Lokan concentrations. Formulation B, containing 40% Lokan, emerged as the most accepted variant based on appearance, color, texture, flavor, odor, and overall acceptability. Physicochemical analysis revealed formulation B to have 71.20% moisture, 2.17% ash, 16.69% crude protein, 0.76% crude fat, and 8.98% carbohydrate content. Lokan addition inversely affected moisture and fat while positively influencing ash, protein, and carbohydrate content. Incorporating Lokan also impacted KSFC hardness and lightness, with increased Lokan correlating with higher hardness and reduced lightness. In conclusion, the successful creation of Lokan-infused fish cakes represents a promising stride in innovating with underutilized resources, presenting new possibilities for diverse and sustainable food products.
Keywords: Polymesoda expansa; Korean-style Fish Cake; Sensory Analysis; Chemical properties; Physical properties